Defending the city, defending votes: campaign strategies in urban Ghana*. Issue 4 (23rd November 2017) - Klaus, Kathleen; Paller, Jeffrey W.
Abstract: Rapid urbanisation in African democracies is changing the way that political parties engage with their constituents, shifting relations between hosts and migrants. This article examines the strategies that parties use to maintain and build electoral support in increasingly diverse contexts. Drawing on in-depth interviews and ethnographic research in Accra, Ghana, we find that some urban political parties rely on inclusive forms of mobilisation, promoting images of cosmopolitanism and unity to incorporate a broad grassroots coalition. Yet in nearby constituencies, parties respond to changing demographics through exclusive forms of mobilisation, using narratives of indigeneity and coercion to intimidate voters who 'do not belong'. Two factors help explain this variation in mobilisation: incumbency advantage and indigene dominance. In contrast to most scholarship on ethnicity and electoral politics in Africa, we find that these varying mobilisation strategies emerge from very local neighbourhood-level logics and motivations.